Political Vanity : Adam Ferguson on the Moral Tensions of Early Capitalism - Arbo, Matthew B. (Book collections on Project MUSE., 2014)
Political Vanity aims to illuminate the central debates over the historical, moral, and political legitimacy of market capitalism as though still profoundly theological in character. This theological sensitivity is achieved by keeping conversation with central theorists of the Scottish Enlightenment, in particular the philosopher and sociologist Adam Ferguson. Ferguson was a contemporary of Hume and Smith, and actively questioned many of the pillars of early capitalism on theological grounds.